Social Movements in Juvenile Prisons: An Investigation. - Cox, Alexandra L. (Social Justice, 2020)
This article investigates the absence of social movements in juvenile prisons through a critical analysis of the legal landscape, behavioral change, and educational practices that exist in contemporary juvenile prisons. The article mines those laws and practices for the ways that they prevent and inhibit young people's organized and collective resistance, but does not evacuate the possibilities for refusal and critique. It also points to a historical case study of the role of collective resistance in juvenile facilities in the 1960s and the systemic efforts to repress those forms of resistance.